Mengembangkan Alat Eksperimen Tumbukan Berbasis Induksi Magnet Dengan Audacity - Lutfia Nurlaili; Thoha Firdaus; Fatkhur Rohman (U-Teach: Journal Education of Young Physics Teacher, 2022)
This Research and Development (R&D) research with Plomp design was aimed to develop a magnetic induction-based collision experiment with audacity. The object of this experiment is acrylic and wood. The results of the development were assessed by media experts, material experts, and 10th-grade high school students. Data collection used a questionnaire on the eligibility of media experts, material experts, and user feasibility trials. The results showed the average validity score of media experts and material experts was 0.77 with a moderate level of validity. While the results of the practicality test by students showed the scores for the practicum tool were 92.9%, 87.25% for the practicum module, and 86% for the user manual, all of which fit into the proper criteria. The percentage of relative error of acrylic and wood for a distance of 10 cm is 0.35% and for a distance of 15 cm is 0.45%. Based on these data, it can be concluded that this magnetic induction-based collision experiment tool with audacity is valid and practical to use as a learning medium.